Virtual Reality in the Treatment of Adults with Chronic Low Back Pain: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Beatriz Brea-Gómez (MDPI AG, 2021)
Virtual reality (VR) can present advantages in the treatment of chronic low back pain. The objective of this systematic review and meta-analysis was to analyze the effectiveness of VR in chronic low back pain. This review was designed according to PRISMA and registered in PROSPERO (CRD42020222129). Four databases (PubMed, Cinahl, Scopus, Web of Science) were searched up to August 2021. Inclusion criteria were defined following PICOS recommendations. Methodological quality was assessed with the Downs and Black scale and the risk of bias with the Cochrane Risk of Bias Assessment Tool. Fourteen studies were included in the systematic review and eleven in the meta-analysis. Significant differences were found in favor of VR compared to no VR in pain intensity postintervention (11 trials; n = 569; SMD = −1.92; 95% CI = −2.73, −1.11; p < 0.00001) and followup (4 trials; n = 240; SDM = −6.34; 95% CI = −9.12, −3.56; p < 0.00001); and kinesiophobia postintervention (3 trials; n = 192; MD = −8.96; 95% CI = −17.52, −0.40; p = 0.04) and followup (2 trials; n = 149; MD = −12.04; 95% CI = −20.58, −3.49; p = 0.006). No significant differences were found in disability. In conclusion, VR can significantly reduce pain intensity and kinesiophobia in patients with chronic low back pain after the intervention and at followup. However, high heterogeneity exists and can influence the consistency of the results.